FAMILY AND EXTERNAL SOCIAL ENVIRONMENT (Academicia Globe: Inderscience Research, 2022)
We know that every change in society goes to the family. When a family has a good social environment, it has the same effect on society. Through this article, we can see how the external social environment affects the family and the changes that take place in this country. A person changes throughout his life. He will develop both socially and mentally, and if the upbringing of the child is appropriate, he will develop as a member of society and take his rightful place in a complex system of social relations. Because development is influenced by education.